PENGARUH KONDISI EKONOMI KELUARGA TERHADAP TINGKAT PENDIDIKAN ANAK DI DESA SIHABORGOAN BARUMUN - Mara Judan Rambey (LPPM Universitas Nias Raya, 2022)
This study aims to find out whether there is a significant influence between family economic conditions on children's education levels. For this reason, this study includes two variables, namely family economic conditions as variable X and the level of education of children variable Y. This research was conducted at Sihaborgoan Barumun Jl. Binanga, Barumun Tengah District, Padang Lawas Regency. The population in this study is the entire sihaborgoan Barumun village community, and the sampling method used in this study is incidental sampling or coincidentally, the sample taken in this study is as many as 30 people. In analyzing the data, guttman scale method questionnaires were used for family economic conditions (variable X) and variable child education level (Y). Then the results are analyzed with inferential analysis. From the results of the analysis obtained the average value of family economic conditions is 84.5 in the category of